Fundamentals of electrical engineering - Bobrow, Leonard S. (New York : Holt, Rinehart and Winston, Inc., 1984)
This book is intended to be the text for a first course in electrical engineering.
Part I. Circuits -- Part II. Electronics -- Part III. Digital systems -- Part IV. Electromechanics.
Includes index.
Keywords: ELECTRICAL ENGINEERING